Human allograft refractive lenticular implantation for high hyperopiccorrection. Issue 2 (February 2020) - Moshirfar, Majid; Hopping, Grant C.; Somani, Anisha N.; Vaidyanathan, Uma; Liu, Harry; Barnes, James R.; Linn, Steven; Ronquillo, Yasmyne C.; Hoopes, Phillip C.
Abstract : Hyperopia is a common form of refractive error in the United States. Many refractive errors can be treated with refractive surgery methods such as laser in-situ keratomileusis and photorefractive keratectomy; however, in patients with large degrees of hyperopia (≥+5.0 diopters [D]), these surgical methods are limited because of higher rates of refractive regression. Lenticule Intrastromal Keratoplasty (LIKE) is a surgical procedure that can be used to correct refractive errors in patients with high hyperopia. The authors describe the first intrastromal implantation of an allograft lenticule performed for the primary correction of hyperopia in the United States, and demonstrate that LIKE is potentially an effective procedure for the correction of high hyperopia. Mechanisms for achieving the intended refractive correction and the complications our patient experienced, including epithelial ingrowth and flap necrosis, are discussed.